FORMULASI DAN UJI MUTU FISIK GRANUL EFFERVESCENT DARI TEMULAWAK (Curcuma xanthorrhiza Roxb) - Rusmin (Akademi Farmasi Yamasi Makassar, 2025)
Abstract. Curcuma (Curcuma xanthorrhiza Roxb) is a leading Indonesian medicinal plant that needs to be developed and utilized. Temu buffoonery contains various chemical compounds, starch is one of the most abundant ingredients found in the temu buffoonery plant. This research aims to formulate Curcuma (Curcuma xantoriza Roxb) rhizome, citric acid, tartaric acid, sodium bicarbonate, lactose, 70% alcohol and to test the physical quality of the preparation which includes organoleptic test, flow time test, soluble time test, water content test. , and the pH test resulted that the effervescent granule preparation met the physical quality requirements as a good effervescent preparation. Based on the research results, the best formula concentration data was obtained in each physical quality test of the preparation, namely formula III with a binder concentration of 6% (P <0.05), with an average flow time (9.20 seconds), dissolution time (3.46 minutes) , moisture content (0.54%), pH (6.86). This reaffirms that the research has successfully developed a granular effervescent formulation from Curcuma (Curcuma xanthorrhiza Roxb) that meets physical quality standards, especially in Formula III with a 6% binding concentration. This achievement opens up opportunities for a broader utilization of traditional Indonesian medicinal plants in a more modern and effective form. Furthermore, this finding also emphasizes the need for further research, which can focus on exploring the bioactive potential of Curcuma and further formulation innovation.